2019
DOI: 10.1111/jace.16335
|View full text |Cite
|
Sign up to set email alerts
|

On the synchronicity of flash sintering and phase transformation

Abstract: There is growing evidence that oxides of complex chemistries can be formed in one step by reactive flash sintering of their elemental constituents. Here we explore the temporal relationship between phase transformation and sintering by combining measurements of sintering with in situ measurements of phase transformation. The experiments are carried out under current rate, where flash is induced by injecting current and increasing it at a constant rate. We show that phase transformation of powders of magnesia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
16
0
3
Order By: Relevance
“…1 Flash sintering has been shown to be an enabling method for making phase pure bismuth ferrite in a few seconds at low furnace temperatures, in ambient air. 5 In the present work, reactive flash sintering is expanded to LLZO(Al) which is constituted from oxides of Li, La, Zr, and Al. 3 Similarly mixtures of alumina and magnesia have been shown to form single phase spinel 4 ; in situ experiments have shown that in this case, phase transformation is completed a little sooner than sintering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Flash sintering has been shown to be an enabling method for making phase pure bismuth ferrite in a few seconds at low furnace temperatures, in ambient air. 5 In the present work, reactive flash sintering is expanded to LLZO(Al) which is constituted from oxides of Li, La, Zr, and Al. 3 Similarly mixtures of alumina and magnesia have been shown to form single phase spinel 4 ; in situ experiments have shown that in this case, phase transformation is completed a little sooner than sintering.…”
Section: Introductionmentioning
confidence: 99%
“…3 Similarly mixtures of alumina and magnesia have been shown to form single phase spinel 4 ; in situ experiments have shown that in this case, phase transformation is completed a little sooner than sintering. 5 In the present work, reactive flash sintering is expanded to LLZO(Al) which is constituted from oxides of Li, La, Zr, and Al. The elemental oxides are shown to transform, and sinter, into the cubic phase with a reasonable value of Li+ conductivity at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the expected chemical reactions in the multicomponent oxide system subjected to RFS are dictated by the corresponding liquidus temperatures between the melting oxide and the rest of the components in the multicomponent phase diagram. Recently, Yoon et al [37] used pure 0.2 μm Al 2 O 3 particles with 1 μm MgO powders mixed with 50 vol.% of nanometric 8YSZ (ZrO 2 stabilized with 8 mol.% Y 2 O 3 ) to form spinel (MgAl 2 O 4 ) by reactive flash sintering at 960 °C at increasing current mode [38]. They recorded the densification and the phase transformation using in-situ X-ray diffraction.…”
Section: Discussionmentioning
confidence: 99%
“…They recorded the densification and the phase transformation using in-situ X-ray diffraction. Although 8YSZ was used to initiate (′ignite′) the flash, no peaks from this oxide were recorded during the course of the experiment where phase transformation preceded the sintering [37]. One should note that chemical reactions are associated with activation energies of a few hundreds of KJ⋅mol −1 compared to a few KJ⋅mol −1 involved in sintering.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sample temperature has been calculated using the black body radiation (BBR) model 1,5,6,11‐13 . The BBR model has been found to agree well with other methods of determining the sample temperature (such as monitoring Pt peaks during in situ X‐ray diffraction (XRD) experiments), but the accuracy is dependent on selecting the appropriate emissivity value 13,14 . Other limitations of the BBR model are discussed in the Results and discussion section.…”
Section: Introductionmentioning
confidence: 93%